2011
DOI: 10.21825/vdt.87269
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain imaging: a brief overview of imaging techniques and their use in human and canine anxiety research

Abstract: When used in combination with specific radioactive markers, functional imaging modalities such as Single Photon Emission Computed Tomography (SPECT) and Positron Emission Tomography (PET) enable the visualization of several neurotransmitter receptors and transporters, as well as of the perfusion and metabolism of the brain.This paper gives an overview of the functional imaging techniques, as well as of the studies that have been performed on humans and canines with anxiety disorders. Thus far, most of the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Furthermore, the occipital brain regions also play a role in the processing of emotionally-relevant visual information, such as stimuli associated with threat or danger, which may contribute to the development or maintenance of anxiety symptoms and disorders 66 , 75 , 77 . For instance, occipital cortical 5-HT2A receptor down-regulation relating to an hyperactive serotonergic system has been found in dogs with anxiety disorders 6 . Of interest compared with healthy controls, Yang et al 14 found decreased nodal degree in the occipital brain areas of structural connectome in (human) patients with generalized anxiety disorder, which demonstrated stronger sensitivity and over-processing of emotional visual information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the occipital brain regions also play a role in the processing of emotionally-relevant visual information, such as stimuli associated with threat or danger, which may contribute to the development or maintenance of anxiety symptoms and disorders 66 , 75 , 77 . For instance, occipital cortical 5-HT2A receptor down-regulation relating to an hyperactive serotonergic system has been found in dogs with anxiety disorders 6 . Of interest compared with healthy controls, Yang et al 14 found decreased nodal degree in the occipital brain areas of structural connectome in (human) patients with generalized anxiety disorder, which demonstrated stronger sensitivity and over-processing of emotional visual information.…”
Section: Discussionmentioning
confidence: 99%
“…As in humans, the prevalence of anxiety disorders in dogs is high, and it is the most common behavioral disorder in daily veterinary practice 5 . It can be confidently stated that anxiety in dogs is a serious welfare problem, not only for the welfare of the animal, but it may also jeopardize the relationship with the owner, leading to abandonment, rehoming or even euthanasia 6 . In the case of comorbid aggression, anxious behavior can pose safety risks, not only to other animals but also to humans.…”
mentioning
confidence: 99%